Remittances : An Automatic Output Stabilizer? - Hakura, Dalia (IMF Working Papers; Working Paper ;, 2009)
Remittance flows appear to be falling worldwide for the first time in decades as a result of the ongoing financial turmoil. It is suspected that the drop in remittance income into developing and emerging markets will have a destabilizing effect on these economies. The paper estimates the impact of remittances on output stability for countries that are dependent on these income flows. Using a sample of 70 countries, including 16 advanced economies and 54 developing countries, we find robust evidence that remittances have a negative effect on output growth volatility of recipient countries. This result supports the notion that remittance flows are a stabilizing influence on output. Thus, the fall in remittances precipitated by the ongoing global financial crisis could potentially increase output variability in recipient countries. This would present a hard challenge for governments in those countries already suffering from the crisis: they must resort to an already stressed and limited set of policy instruments, such as fiscal policy, to counter the resulting adverse economic and social impacts of lower remittances.